Herança da resistência dos acessos pi 313970 e pi 414723 a podosphaera xanthii em meloeiro - Loureiro, Francisco Leandro Costa (Universidade Federal Rural do Semi-Árido, 2019)
Powdery mildew is one of the most severe diseases affecting shoots of the melon caused by Podosphaera xanthii. One of the most widely used alternatives for control pathogen is the use of genetic resistance. Thus, studies to genetic control of the resistance are essential for introgression of resistance alleles in breeding programs to obtain resistant cultivars. The objective of the present work was to investigate the inheritance of resistance of access melon PI 313970 e PI 414723 to Podosphaera xanthii races 5, Br06 and 3.5. Two experiments were conducted each one referring to the study of inheritance for each access. The F1 and F2 populations generated by two crosses (PI 313970 x ‘Goldex’) and (PI 414723 x ‘Goldex’) were evaluated as well as the parents. The inoculation was performed at 20 days after sowing. Evaluations occurred 10 days after inoculation in each trial using a scale of 1 to 4 grades, being resistant those plants scored 1 and 2 and susceptible those scored 3 and 4. To validate genetic models involved in resistance, a Chi-square test (χ2) was performed using the phenotypic frequencies of resistant and susceptible individuals. Segregation in the F2 generations revealed four genetic models involved in the resistance of the accessions to powdery mildew. In PI accession 313970 a gene was verified controlling resistance to race 5, two genes with recessive and dominant epistasis responsible for resistance to BR06 and dual recessive epistasis responsible for resistance to race 3.5. In PI accession 414723 digenic inheritance was found with dual recessive epistasis responsible for resistance to races 5 and BR06 and a dominant gene causing resistance to race 3.5
Keywords: Controle genético; Cucumis melo; Epistasia; Monogenia; Oídio; Genetic control; Cucumis melo; Epistasis; Monogeny; Powdery mildew; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA